PEMBERDAYAAN MASYARAKAT DALAM PEMBANGUNAN PARIWISATA BERBASIS MASYARAKAT (COMMUNITY-BASED TOURISM) MELALUI KELOMPOK SADAR WISATA - nurrahman, faris; ., Turtiantoro; manar, ghulam (Journal of Politic and Government Studies, 2018)
ABSTRACTThe policy of tourism development since Indonesian independence in 1945 until now has changed along with the changing socio-political and economic conditions in Indonesia and the world. Community-based tourism or CBT is a concept of tourism management by prioritizing the participation of the local community with the purpose to provide welfare for them while maintaining the quality of the environment and protecting social and cultural life.Desa Wisata Wiskuno is an example of a tourism destination that implements the concept of CBT in the tourism development model. Desa Wisata Wiskuno was established on 26 September 2016 managed by Pokdarwis Sumbermadu that located in Maduretno Village, Kebumen Distict. Over the course of 2 years, Pokdarwis Sumbermadu succeeded in mobilizing community participation and received several awards in District and Province level which enabled them to gain the Government's attention to help the Pokdarwisâ€™s program in mobilizing people's participation in tourism development.The researcher used qualitative descriptive method and applied interview and documentation study in collecting data in Maduretno Village, development location of Desa Wisata Wiskuno conducted by the local community and Pokdarwis Sumbermadu.The result of this research is â€œHow Pokdarwis Sumbermadu to achieve success in applying the concept of CBT at Maduretno Village by established Desa Wisata Wiskunoâ€.Recommendations that can be given is Pokdarwis Sumbermadu is expected to make more varied programs according with tourism development, and increasing its role to apply Sapta Pesona values to the local community. The local government of Kebumen District can continue to provide coaching support, and tourism-related training on Pokdarwis Sumbermadu.Keywords: Tourism, Tourism Development, Community Based Tourism, Desa Wisata, Kelompok Sadar Wisata